Dust detection from ground‐based observations in the summer global dust maximum: Results from Fennec 2011 and 2012 and implications for modeling and field observations. Issue 3 (4th February 2015) - Allen, Christopher J. T.; Washington, R.; Saci, A.
Abstract In boreal summer, the central Sahara is the dustiest place on Earth. Fennec supersite 1 is located within the dust maximum. With two field seasons completed, June 2011 (intensive observation period (IOP) 1) and June 2012 (IOP2), we now have an initial measure of their representativeness. Although the number of dust event hours in IOP2 is up to 169 h (60%) more than in IOP1, the relative importance of the different dust mechanisms is the same. In both years, emission by cold pool outflows from deep convection causes most dust, followed by dust advection, monsoon surges, low‐level jet emission and lastly dry convective plumes. Given the dominance of cold pools, it is very important that they be incorporated in dust modeling efforts over the region. Because cold pools frequently occur at night and are associated with cloud cover, instruments that can monitor in these conditions are particularly valuable in this region. Sun photometer aerosol optical depth retrievals, for example, are only available for 23% (41%) of the time cold pool emission occurs at the supersite in IOP1 (IOP2). Deployment of instrumentation in remote regions being difficult and expensive, choosing the optimal instrument payload pays dividends. With this motivation, we evaluate the different dust detection instrumentation deployed at the supersite and develop an approach which can identify and characterize individual dust emission mechanisms with a high degree of success purely from routine meteorological observations and remote sensing. This identification is, however, much more challenging in the case of dust advection.